Achieving Gaussian outputs from large-mode-area higher-order-mode fibers - Lindlein, Norbert; Leuchs, Gerd; Ramachandran, Srinivasan (Applied Optics, 2007)
We describe an alternative to fiber-gratings for converting higher-order LP0om (m > 1) fiber modes into a nearly fundamental Gaussian shape at the output of a fiber. This schematic enables the use of light propagation in higher-order modes of a fiber, a fiber-platform that has recently shown great promise for achieving very large mode areas needed for future high-power lasers and amplifiers. The conversion will be done by using a binary phase plate in the near field of the fiber, which emits the LPom mode. Since the binary phase plate alone cannot increase the quality factor M2 of the laser beam because of some broad sidebands, a filtering of the sidebands is done in the Fourier plane of a telescope. Of course, this will cost some of the total light power, but on the other side the M2 factor can be reduced to nearly the ideal value near 1.0, and it is shown that ∼76% of the total light power can be conserved for all investigated modes (2≤m≤8). A tolerance analysis for the phase plate and its adjustment is made, and different optical imaging systems to form a magnified image of the fiber mode on the phase plate are discussed in order to have more tolerance for the adjustment of the phase plate. © 2007 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.achiev